2004
DOI: 10.1074/jbc.m312042200
|View full text |Cite
|
Sign up to set email alerts
|

Exocytotic Insertion of TRPC6 Channel into the Plasma Membrane upon Gq Protein-coupled Receptor Activation

Abstract: TRPC proteins are the mammalian homologues of the Drosophila transient receptor potential channel and are involved in calcium entry after agonist stimulation of non-excitable cells. Seven mammalian TRPCs have been cloned, and their mechanisms of activation and regulation are still the subject of intense research. TRPC proteins interact with the inositol 1,4,5-trisphosphate receptor, and the conformational coupling plays a critical role in the activation of calcium entry. Some evidence also supports an exocytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(138 citation statements)
references
References 61 publications
8
128
2
Order By: Relevance
“…We also examined TRPC6 because a microarray analysis suggested that it was up-regulated in T1R3 knockdown cells. Carbachol is capable of inducing ROCE by activating and promoting cell surface expression of TRPC6 downstream of muscarinic receptor binding (26,27). Although the suspected change in its mRNA could not be validated, TRPC6 seemed a logical candidate and may be involved in some manner we did not detect (23,24).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…We also examined TRPC6 because a microarray analysis suggested that it was up-regulated in T1R3 knockdown cells. Carbachol is capable of inducing ROCE by activating and promoting cell surface expression of TRPC6 downstream of muscarinic receptor binding (26,27). Although the suspected change in its mRNA could not be validated, TRPC6 seemed a logical candidate and may be involved in some manner we did not detect (23,24).…”
Section: Discussioncontrasting
confidence: 45%
“…Calcium entry occurring through plasma membrane channels as a result of GPCR activation independent of the state of Ca 2ϩ i stores is referred to as ROCE (25). It has been demonstrated that carbachol is capable of inducing ROCE by activating and promoting cell surface expression of TRPC6 downstream of muscarinic receptor binding (26,27). Expression of neither RGS4 nor TRPC6 was significantly different in T1R3 knockdown cells compared with the control, suggesting that the enhanced carbachol response was not a result of decreased RGS4 or increased TRPC6 expression (Fig.…”
Section: Carbachol-induced Changes In Camentioning
confidence: 99%
“…The presence of a channel at the cell membrane must be tightly controlled to ensure correct timing and duration of signals relayed by such proteins. Activation of several channels belonging to the TRP family of channels correlates with their increased appearance at the plasma membrane (53)(54)(55). The molecular nature of AA-activated, calcium-permeable channels in the plasma membrane is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported translocation of TRPC3 in response to stimulation of the EGF receptor but failed to observe translocation of TRPC3 in response to M3 receptor stimulation [50]. Stimulation of the M3 receptor causes the translocation of TRPC6 to the plasma membrane [51], and stimulation EGF receptor caused the translocation of TRPC4 [52] and TRPC5 [53] to the plasma membrane. The PI3-kinase pathway and its downstream effector Rac1 are implicated in the EGFstimulated translocation of TRPC5 [53], which may be a general mechanism mediating Tyrosine kinase receptor mediated translocation of TRPC channels.…”
Section: Homer1 and Translocation Of Trpc Channelsmentioning
confidence: 99%